1995
DOI: 10.1111/j.1440-1800.1995.tb00164.x
|View full text |Cite
|
Sign up to set email alerts
|

Art, science and social science in nursing: occupational origins and disciplinary identity

Abstract: This paper forms part of a wider study examining the history and sociology of nursing education in England between 1860 and 1948. It argues that the question of whether nursing was an art, science and/or social science has been at the 'heart' of a wider debate on the occupational status and disciplinary identity of nursing. The view that nursing was essentially an art and a 'calling', was championed by Florence Nightingale. Ethel Bedford Fenwick and her allies insisted that nursing, like other professions, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 6 publications
1
8
0
1
Order By: Relevance
“…The establishment of nursing departments in faculties of social science, and the strong links that some early departments had with community medicine, has favoured the cultivation of research traditions in these fields (Rafferty, 1995b), Nevertheless, we need to confront the questions of how to build upon the existing intellectual capital and, in particular, how to build a balanced portfolio of skill with which to engage in the multidisciplinary arena. Any consideration of research in and for nursing needs to be examined within the context of the social, economic, political and intellectual forces that have shaped, and will continue to shape, its trajectory.…”
Section: Resultsmentioning
confidence: 99%
“…The establishment of nursing departments in faculties of social science, and the strong links that some early departments had with community medicine, has favoured the cultivation of research traditions in these fields (Rafferty, 1995b), Nevertheless, we need to confront the questions of how to build upon the existing intellectual capital and, in particular, how to build a balanced portfolio of skill with which to engage in the multidisciplinary arena. Any consideration of research in and for nursing needs to be examined within the context of the social, economic, political and intellectual forces that have shaped, and will continue to shape, its trajectory.…”
Section: Resultsmentioning
confidence: 99%
“…58 The new occupational roles of lady principal and lady superintendent did not explicitly threaten existing gender boundaries in the public sphere, since the lady principals and lady superintendents were responsible, respectively, for the management of the school and the hospital household, and as such, the new roles represented a translocation of the domestic hierarchy into the school and the hospital. 59 Nevertheless, in occupying these new female management roles and in their respective professionalising projects, the lady principals and lady superintendents did implicitly challenge existing gender boundaries. Occupying salaried professional roles in the public sphere, the lady principals and lady superintendents were operating at a management level in a male-dominated world, a world in which there were few other examples of such public professional roles for middle-class women.…”
Section: Discussionmentioning
confidence: 99%
“…Considerations of nursing education as a disciplining education and of the view of order as a central issue have been discussed based on a Foucauldian approach in several studies (Rafferty 1995; Buus 2002). In this study, it is suggested that the body of knowledge surrounding the nurse‐to‐be offered her a position as orderly and played a role in regulating her conduct, along with other practices in the field of nursing education.…”
Section: Discussionmentioning
confidence: 99%